Pengaruh Kompetensi, Self-Efficacy, Disiplin dan Lingkungan Kerja terhadap Kinerja Karyawan RSUD S.K. Lerik Kupang di Moderasi Kepuasan - Wiwin Ottu; Frans Gana; Maria Lino (Policy, Law and Political Research Center, 2025)
This study aims to analyze the influence of HR competency, self-efficacy, work discipline, and non-physical work environment on employee performance, with job satisfaction as a moderating variable at SK Lerik Kupang Regional General Hospital. The study sample consisted of 203 randomly selected employees, with data collected through questionnaires and analyzed using Partial Least Square (PLS), this method is strong in predicting the relationship between latent variables and their indicators. The results showed that competency, self-efficacy, work discipline, and non-physical work environment had a positive and significant effect on employee performance. Meanwhile, job satisfaction was proven to have a direct effect on performance, but did not moderate the relationship between the four variables and employee performance. This finding confirms the importance of improving competency, discipline, self-efficacy, and the quality of the work environment in driving performance, while job satisfaction plays a more independent role.